Working papers of a three-day short course on high voltage technology, 7-9 November 2000, Universiti Teknologi Malaysia, Skudai, Johor - A three-day short course on high voltage technology: (2000 : Skudai, Johor); Universiti Teknologi Malaysia. Fakulti Kejuruteraan Elektrik. Institut Voltan dan Arus Tinggi (Skudai : Universiti Teknologi Malaysia, 2000)
15